Synthesis, Characterization, and Antibacterial Studies of Mixed Ligand Dioxouranium Complexes with 8-Hydroxyquinoline and Some Amino Acids. (27th September 2011) - Patil, Sunil S.; Thakur, Ganesh A.; Shaikh, Manzoor M.
Abstract : Mixed ligand complexes of dioxouranium (VI) of the type [UO2 (Q)(L)·2H2 O] have been synthesized using 8-hydroxyquinoline (HQ) as a primary ligand and amino acids (HL) such as L-threonine, L-tryptophan, and L-isoleucine as secondary ligands. The metal complexes have been characterized by elemental analysis, electrical conductance, magnetic susceptibility measurements, and spectral and thermal studies. The electrical conductance studies of the complexes indicate their nonelectrolytic nature. Magnetic susceptibility measurements revealed diamagnetic nature of the complexes. Electronic absorption spectra of the complexes show intraligand and charge transfer transitions, respectively. Bonding of the metal ion through N- and O-donor atoms of the ligands is revealed by IR studies, and the chemical environment of the protons is confirmed by NMR studies. The thermal analysis data of the complexes indicate the presence of coordinated water molecules. The agar cup and tube dilution methods have been used to study the antibacterial activity of the complexes against the pathogenic bacteria S. aureus, C. diphtheriae, S. typhi, and E. coli .